RESEARCH METHODS FOR CHANGES IN SOIL SALINITY, SEEPAGE WATER LEVEL, AND SEEPAGE WATER MINERALIZATION IN THE SYRDARYA REGION (Scientific journal of the Fergana State University, 2023)
Recent research has demonstrated that the geographical mapping, tracking, assessment, and monitoring of soil salinity, seepage water levels, and seepage water mineralization may be effectively accomplished by integrating conventional approaches with geoinformation systems methods. Geoinformation systems provide you the ability to validate the veracity of GIS-based findings and promote the findings of subsequent field studies.